2019
DOI: 10.1039/c9nr05285b
|View full text |Cite
|
Sign up to set email alerts
|

Metallic filamentary conduction in valence change-based resistive switching devices: the case of TaOx thin film with x ∼ 1

Abstract: A detailed study of the electrical transport in TaOx thin films with x ∼ 1 provides an insight into the conduction in conductive filaments inside Ta2O5-based resistive switching devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 75 publications
0
19
0
Order By: Relevance
“…The devices are programmed by applying electrical stimuli, during which an n-conducting filament consisting of mobile donors is either formed (SET) or ruptured (RESET). Spectroscopic studies have identified these mobile donors as oxygen vacancies. Especially for TaO x -based devices also a movement of metallic cations was observed. During the SET, a negative voltage is applied to the active electrode (attracting mobile donors) and a positive voltage during the RESET (repelling mobile donors). As the voltages required for the SET and RESET have opposite signs, this corresponds to a bipolar switching mode.…”
Section: Introductionmentioning
confidence: 99%
“…The devices are programmed by applying electrical stimuli, during which an n-conducting filament consisting of mobile donors is either formed (SET) or ruptured (RESET). Spectroscopic studies have identified these mobile donors as oxygen vacancies. Especially for TaO x -based devices also a movement of metallic cations was observed. During the SET, a negative voltage is applied to the active electrode (attracting mobile donors) and a positive voltage during the RESET (repelling mobile donors). As the voltages required for the SET and RESET have opposite signs, this corresponds to a bipolar switching mode.…”
Section: Introductionmentioning
confidence: 99%
“…This also appears to be unlikely. Recent conductivity measurements of substoichiometric TaO x films indicate that the compositions that can produce significant current densities and Joule heating in the filament at typical applied voltage values are close to 1:1, i.e., composition of TaO. , …”
Section: Discussionmentioning
confidence: 99%
“…Unlike traditional silicon‐based memory devices with binary memory states, organic resistive memory devices possess multiple resistive states which enhance their data storage capacity [16] . There are many switching (between the conduction states) mechanism proposed and established in organic devices, mainly categorized into thermochemical reaction, ion migration, interfacial reaction, charge trapping/de‐trapping, charge transfer, electrochemical redox reaction, and conformational change [17–21] . If the states can retain the assigned binary states for longer duration and in the absence of an applied potential, it is called a non‐volatile resistive memory device [22,23] .…”
Section: Introductionmentioning
confidence: 99%